The impact of cultural context on the perception of work/family balance by professional women in Singapore and Hong Kong - Thein, Htwe Htwe; Austen, Siobhan; Currie, J.; Lewin, E. (Sage Publications, 2010)
‘Work/family balance’ has recently come to the fore in public policy debate and academic inquiry across the industrialized world. However, this issue has been relatively under-explored in the context of Asian business and society. This paper reports the results of a qualitative, exploratory investigation of the perceptions and experiences of predominantly professional women, aged 25—45 years living in Singapore and Hong Kong. Data from focus groups were used to explore how women in these countries perceive work/family balance and the role of family, government and other support structures in managing this aspect of their lives. This study confirms that cultural context is a significant factor in how women perceive and respond to the issue of work/family balance.